Economic Plants of Tripura State Timber Yielding Plants Principal uses - Deb, D. B. (Indian Forester, 1975)
The present paper on 'Timber yielding plants : principal uses' is part I of a series entitled 'Economic Plants of Tripura State'. This series is based on Botanical Survey of the State by the author since 1956 and study of enormous scientific literature on uses of plants. It is an attempt to assess the economic potential of the vegetable resources of the state. The useful plants are grouped from a utilitarian point of view. Timber yielding plants are treated in two papers. Plants which are used for construction of houses, bridges, ships, boats, carriages, wagons, trucks and buses, railway sleepers, electric transmission poles, carpentry and cabinet making etc., and are found in Tripura State are named in this paper.